Future Time Perspective Impacts Gain-Related but Not Loss-Related Intertemporal Choice - Li, Tian; Tan, Yuxin; Gong, Xianmin; Yin, Shufei; Qiu, Fangshu; Hu, Xue (Frontiers in Psychology, 2018)
Future time perspective (FTP) modulates individuals’ temporal orientation in selecting their motivations and goals, which widely influences their cognitions and behaviors. However, it remains unclear how FTP exactly affects intertemporal choice. To clarify the effect of FTP on intertemporal choice, 90 college students (Mage = 21.70, SD = 1.23) were randomly assigned to the limited FTP condition (16 males, 29 females) and the open-ended FTP condition (17 males, 28 females). In the limited FTP condition, participants were instructed to imagine their states of being 70 years old, whereas in the open-ended FTP condition, they were instructed to describe their current states. All participants then completed a series of intertemporal choice tasks, in which they chose from gain- and loss-related choices occurring at various time points. Results showed that the participants who received the future-imagining manipulation had more limited FTP compared with those who did not receive the manipulation, which confirmed the validity of the FTP manipulation. A 2 (FTP: limited vs. open-ended) × 2 (type of choice: gain vs. loss) repeated measures ANOVA on discount rate revealed a significant interaction between these two factors. The participants in the limited FTP condition had higher discount rates on gain-related choices but showed no difference on loss-related choices compared with the participants under the open-ended FTP condition. The results suggest that limited FTP could lower individuals’ future orientation (i.e., willingness to delay an outcome) on gain-related, but not on loss-related, intertemporal decision-making.